2012
DOI: 10.1073/pnas.1200785109
|View full text |Cite
|
Sign up to set email alerts
|

Conserved and essential transcription factors for cellulase gene expression in ascomycete fungi

Abstract: Rational engineering of filamentous fungi for improved cellulase production is hampered by our incomplete knowledge of transcriptional regulatory networks. We therefore used the model filamentous fungus Neurospora crassa to search for uncharacterized transcription factors associated with cellulose deconstruction. A screen of a N. crassa transcription factor deletion collection identified two uncharacterized zinc binuclear cluster transcription factors (clr-1 and clr-2) that were required for growth and enzymat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
442
3
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(465 citation statements)
references
References 44 publications
15
442
3
5
Order By: Relevance
“…19) In the present study, we found that ManR regulates not only mannanolytic enzyme genes but also cellulolytic enzyme genes in A. oryzae. Hence the regulatory function of cellulase gene expression is conserved among these orthologous genes, manR, clrB and clr2.…”
Section: 16)mentioning
confidence: 58%
See 1 more Smart Citation
“…19) In the present study, we found that ManR regulates not only mannanolytic enzyme genes but also cellulolytic enzyme genes in A. oryzae. Hence the regulatory function of cellulase gene expression is conserved among these orthologous genes, manR, clrB and clr2.…”
Section: 16)mentioning
confidence: 58%
“…Hence the regulatory function of cellulase gene expression is conserved among these orthologous genes, manR, clrB and clr2. However, although deletion of clrB caused a severe reduction in the production of xylanolytic enzymes in A. nidulans when the ÁclrB mutant was grown in a cultivation medium containing Avicel, 19) disruption of manR did not significantly affect the expression of xylanolytic enzyme genes in A. oryzae when Avicel was used as sole carbon source (data not shown). Hence the system regulating hemicellulase genes in A. oryzae might be different from that in A. nidulans.…”
Section: 16)mentioning
confidence: 96%
“…Alleviation of CCR, either by inactivation of the CreA/CRE1 regulator or by lack of a carbon source in the medium, results in the increase of transcription of genes encoding CAZymes that are active on plant-derived carbohydrates in a number of fungi [42][43][44][45][46][47][48]. A large proportion of these genes was expressed both during carbon starvation conditions and during exposure to lignocellulose for example in N. crassa exposed to Avicel [45] or A. niger exposed to wheat straw [42]. This transcriptional response to carbon starvation results in secretion of enzymes that are active on plant-derived carbohydrates [42].…”
Section: How Fungi Detect Lignocellulosementioning
confidence: 99%
“…That study defined the 'pectin regulon' and compared this to the 'Avicel regulon' from Coradetti et al [45] and the 'xylan regulon' -the xylan study was a replication of the microarray experiment from Sun et al [56] using RNAseq. All three substrates significantly induced a common set of 29 genes and three quarters of these genes encoded CAZymes.…”
Section: Responses Of N Crassa To Polysaccharides and Lignocellulosimentioning
confidence: 99%
“…It is reported that the degradation intensity of cellulase is depends on the transcription regulatory factor. ClrB is a global positive regulator,and ClrB/CLR -2, is essential for cellulase expression in P. oxalicum, N.crassa and Aspergillus nidulans [7,8] . It also belongs to the zinc finger protein transcription factor superfamily.…”
Section: Introductionmentioning
confidence: 99%